2006
DOI: 10.3200/jece.37.1.21-37
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Course Evaluations: Does an Online Delivery System Influence Student Evaluations?

Abstract: An increasing number of academic institutions are considering changing to Web-based systems to take advantage of efficiencies in the collection of end-of-semester course evaluations. In considering such a change it is important that researchers determine whether it will affect mean evaluation scores and response rates. We undertook this study in a department considering changing over to electronic course evaluations to determine the effect such a change would have on the quality of resulting course evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 3 publications
4
88
2
4
Order By: Relevance
“…toute une série d'articles sont actuellement publiés quant aux avantages et aux inconvénients de la passation des questionnaires en ligne ou papier (anderson, Cain, & Bird, 2005 ;avery, Bryant, Mathios, Kang, & Bell, 2006 ;norris & Conn, 2005 ;nulty, 2008). Il ressort des enquêtes menées à ce sujet que les taux de réponse aux questionnaires en ligne sont inférieurs à ceux sous forme de papier, ce qui conduit certaines universités à préférer conserver la modalité traditionnelle.…”
Section: Séduction De La Technologieunclassified
“…toute une série d'articles sont actuellement publiés quant aux avantages et aux inconvénients de la passation des questionnaires en ligne ou papier (anderson, Cain, & Bird, 2005 ;avery, Bryant, Mathios, Kang, & Bell, 2006 ;norris & Conn, 2005 ;nulty, 2008). Il ressort des enquêtes menées à ce sujet que les taux de réponse aux questionnaires en ligne sont inférieurs à ceux sous forme de papier, ce qui conduit certaines universités à préférer conserver la modalité traditionnelle.…”
Section: Séduction De La Technologieunclassified
“…Consequently, evaluation of online courses is a popular topic in the research literature (Dykman & David, 2008;Lord, 2009;Mandernach et.al., 2005;Weschke & Canipe, 2010; Villar Angulo & Alegre de la Rosa, 2007;Avery, Bryant, Mathios, Kang, & Bell, 2006). Distance learning practitioners have struggled to create effective models for designing, assessing, and evaluating online courses.…”
Section: Introductionmentioning
confidence: 99%
“…5, No. 6; measured by grade, cumulative GPA, and SAT score) showed positive association with the likelihood of response (Avery et al, 2006;Porter & Umbach 2006). Adams and Umbach (2012) found that "Not only are students with higher grades typically awarding higher ratings, but they are also the ones who are more likely to respond".…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, female students are more likely to respond than males (Avery et al, 2006;Porter & Umbach, 2006). High performance and achievement (as www.ccsenet.org/hes…”
Section: Literature Reviewmentioning
confidence: 99%